2007
DOI: 10.1261/rna.560307
|View full text |Cite
|
Sign up to set email alerts
|

A loop–loop interaction and a K-turn motif located in the lysine aptamer domain are important for the riboswitch gene regulation control

Abstract: The lysine riboswitch is associated to the lysC gene in Bacillus subtilis, and the binding of lysine modulates the RNA structure to allow the formation of an intrinsic terminator presumably involved in transcription attenuation. The complex secondary structure of the lysine riboswitch aptamer is organized around a five-way junction that undergoes structural changes upon ligand binding. Using single-round transcription assays, we show that a loop-loop interaction is important for lysine-induced termination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
107
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 73 publications
(128 reference statements)
17
107
1
Order By: Relevance
“…Reactions were stopped using an equal volume of formamide loading dye. K switch values were obtained using a procedure similar to that used for T 50 (26,27). The quantification assumes a simple 1:1 stoichiometry between the aptamer and AdoCbl as expected from in-line probing data (10,16).…”
Section: Methodsmentioning
confidence: 99%
“…Reactions were stopped using an equal volume of formamide loading dye. K switch values were obtained using a procedure similar to that used for T 50 (26,27). The quantification assumes a simple 1:1 stoichiometry between the aptamer and AdoCbl as expected from in-line probing data (10,16).…”
Section: Methodsmentioning
confidence: 99%
“…2-Aminopurine Fluorescence Spectroscopy-Fluorescence spectroscopy was performed as described previously (21). The fluorescence data were fitted to a simple two-state model that assumes an all-or-none conformational transition induced by the binding of magnesium ions, with a Hill coefficient n and an apparent association constant K A .…”
Section: Methodsmentioning
confidence: 99%
“…The motif causes the helical path to bend by ∼120°a nd is often the binding site for proteins (Klein et al 2001). K-turns are present in several riboswitch classes, including the Class-I S-adenosylmethionine (SAM-I) and lysine riboswitches, where it has been shown that K-turn integrity is essential for productive folding and ligand recognition (Blouin and Lafontaine 2007;Heppell and Lafontaine 2008). Kladwang et al (2012) and Sherman et al (2012) analyzed the effect that the presence of P0 has on the glycine riboswitch at the local, single-nucleotide level through chemical probing techniques.…”
Section: Introductionmentioning
confidence: 99%